Serotonin mediation of early memory formation via 5-HT2B receptor-induced glycogenolysis in the day-old chick - Gibbs, Marie E.; Hertz, Leif (Frontiers in Pharmacology, 2014)
Investigation of the effects of serotonin on memory formation in the chick revealed an action on at least two 5HT receptors. Serotonin injected intracerebrally produced a biphasic effect on memory consolidation with enhancement at low doses and inhibition at higher doses. The non-selective 5HT receptor antagonist methiothepin and the selective 5HT2B/C receptor antagonist SB221284 both inhibited memory, suggesting actions of serotonin on at least 2 different receptor subtypes. The 5HT2B/C and astrocyte-specific 5-HT receptor agonists, fluoxetine and paroxetine, enhanced memory and the effect was attributed to glycogenolysis. Inhibition of glycogenolysis with a low dose of DAB prevented both serotonin and fluoxetine from enhancing memory during short-term memory but not during intermediate memory. The role of serotonin on the 5HT2B/C receptor appears to involve glycogen breakdown in astrocytes during short-term memory, whereas other published evidence attributes the second period of glycogenolysis to noradrenaline.